This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: u )] =sin( u ) [ x 2 cos( x 2 )] = [ x 2 ] [cos( x 2 )] + [cos( x 2 )] [ x 2 ] Product Rule = [2 x ][cos( x 2 )] + [cos( x 2 )] [ x 2 ] Power Rule = [2 x ][cos( x 2 )] + [sin( x 2 ) 2 x ][ x 2 ] Chain Rule = 2 x cos( x 2 )2 x 3 sin( x 2 ) Simplify 2) f ( x ) = sin(3 x 2 + x ) + x 2 + 1 3) f ( x ) = x 3 tan( x 4 + x ) 4) y = cos(sin(x )) cos(cos(2 x 3 )) 5) g ( x ) = x 3 sin 2 (3 x 2 ) Challenge) f ( x ) = x 2 sin( x 3 ) cos(4 x3) sin(sec( x ))...
View
Full
Document
This note was uploaded on 03/20/2008 for the course M 408c taught by Professor Mcadam during the Spring '06 term at University of Texas at Austin.
 Spring '06
 McAdam
 Derivative, Power Rule

Click to edit the document details